Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Influence of global climate modes on wildfire occurrence in the contiguous United States under recent and future climates - Theodore R. Keeping; Theodore G. Shepherd; I. Colin Prentice; Karin van der Wiel; Sandy P. Harrison (Climate Dynamics, 2026)
Predictable modes of climate variability, such as the El Niño Southern Oscillation (ENSO), have a major influence on regional weather patterns, an important control on wildfire occurrence. Although these global climate modes have been associated with historical variability in wildfire occurrence in the United States and are used to forecast seasonal wildfire risk, precise information about the spatial pattern and magnitude of their influence is lacking and the satellite record of wildfires is too short to address these issues. Here we use wildfire occurrence model with a large ensemble of 1600 simulated years from EC-Earth3 in a recent climate (2000–2009) and a future climate corresponding to + 2 °C global warming, to characterise the impact of specific climate modes on wildfire occurrence in the contiguous US. We show that ENSO, the Indian Ocean Dipole (IOD), and the 1-year lagged Tropical North Atlantic (TNA+1) have the greatest effect on annual fire occurrence—strongly contributed by the effect of these modes on hot, dry conditions in the Great Plains and precipitation in the southwestern US. El Niño is not significantly associated with wildfire occurrence in the northwestern US, contrary to expectation, but is associated with a later (earlier) wildfire season peak in the southwestern (southeastern) US. Under future warming, the AMO and PNA become a significant influence over most of the US, and the magnitude of impact of ENSO and TNA+1 increase strongly.

A General Model for the Seasonal to Decadal Dynamics of Leaf Area - Boya Zhou; Wenjia Cai; Ziqi Zhu; Han Wang; Sandy P. Harrison; I. Colin Prentice (Global Change Biology, 2025)
Leaf phenology, represented at the ecosystem scale by the seasonal dynamics of leaf area index (LAI), is a key control on the exchanges of CO 2 , energy, and water between the land and atmosphere. Robust simulation of leaf phenology is thus important for both dynamic global vegetation models (DGVMs) and land‐surface representations in climate and Earth System models. There is no general agreement on how leaf phenology should be modeled. However, a recent theoretical advance posits a universal relationship between the time course of “steady‐state” gross primary production (GPP) and LAI—that is, the mutually consistent LAI and GPP that would pertain if weather conditions were held constant. This theory embodies the concept that leaves should be displayed when their presence is most beneficial to plants, combined with the reciprocal relationship of LAI and GPP via (a) the Beer's law dependence of GPP on LAI, and (b) the requirement for GPP to support the allocation of carbon to leaves. Here we develop a global prognostic LAI model, combining this theoretical approach with a parameter‐sparse terrestrial GPP model (the P model) that achieves a good fit to GPP derived from flux towers in all biomes and a scheme based on the P model that predicts seasonal maximum LAI as the lesser of an energy‐limited rate (maximizing GPP) and a water‐limited rate (maximizing the use of available precipitation). The exponential moving average method is used to represent the time lag between leaf allocation and modeled steady‐state LAI. The model captures satellite‐derived LAI dynamics across biomes at both site and global levels. Since this model outperforms the 15 DGVMs used in the TRENDY project, it could provide a basis for improved representation of leaf‐area dynamics in vegetation and climate models.

The Response of Carbon Uptake to Soil Moisture Stress: Adaptation to Climatic Aridity - Giulia Mengoli; Sandy P. Harrison; I. Colin Prentice (Global Change Biology, 2025)
The coupling between carbon uptake and water loss through stomata implies that gross primary production (GPP) can be limited by soil water availability through reduced leaf area and/or stomatal conductance. Ecosystem and land‐surface models commonly assume that GPP is highest under well‐watered conditions and apply a stress function to reduce GPP as soil moisture declines. Optimality considerations, however, suggest that the stress function should depend on climatic aridity: ecosystems adapted to more arid climates should use water more conservatively when soil moisture is high, but maintain unchanged GPP down to a lower critical soil‐moisture threshold. We use eddy‐covariance flux data to test this hypothesis. We investigate how the light‐use efficiency (LUE) of GPP depends on soil moisture across ecosystems representing a wide range of climatic aridity. ‘Well‐watered’ GPP is estimated using the sub‐daily P model, a first‐principles LUE model driven by atmospheric data and remotely sensed vegetation cover. Breakpoint regression is used to relate daily β(θ) (the ratio of flux data–derived GPP to modelled well‐watered GPP) to soil moisture estimated via a generic water balance model. The resulting piecewise function describing β(θ) varies with aridity, as hypothesised. Unstressed LUE, even when soil moisture is high, declines with increasing aridity index (AI). So does the critical soil‐moisture threshold. Moreover, for any AI value, there exists a soil moisture level at which β(θ) is maximised. This level declines as AI increases. This behaviour is captured by universal non‐linear functions relating both unstressed LUE and the critical soil‐moisture threshold to AI. Applying these aridity‐based functions to predict the site‐level response of LUE to soil moisture substantially improves GPP simulation under both water‐stressed and unstressed conditions, suggesting a route towards a robust, universal model representation of the effects of low soil moisture on leaf‐level photosynthesis.

Fire-Image-DenseNet (FIDN) for predicting wildfire burnt area using remote sensing data - Bo Pang; Sibo Cheng; Yuhan Huang; Yufang Jin; Yike Guo; I. Colin Prentice; Sandy P. Harrison; Rossella Arcucci (Computers & Geosciences, 2025)

Soil Nitrogen Supply Exerts Largest Influence on Leaf Nitrogen in Environments with the Greatest Leaf Nitrogen Demand - Alissar Cheaib; Elizabeth F. Waring; Risa McNellis; Evan A. Perkowski; Jason P. Martina; Eric W. Seabloom; Elizabeth T. Borer; Peter A. Wilfahrt; Ning Dong; Iain Colin Prentice; Ian J. Wright; Sally A. Power; et al. (Ecology Letters, 2025)
Accurately representing the relationships between nitrogen supply and photosynthesis is crucial for reliably predicting carbon–nitrogen cycle coupling in Earth System Models (ESMs). Most ESMs assume positive correlations amongst soil nitrogen supply, leaf nitrogen content, and photosynthetic capacity. However, leaf photosynthetic nitrogen demand may influence the leaf nitrogen response to soil nitrogen supply; thus, responses to nitrogen supply are expected to be the largest in environments where demand is the greatest. Using a nutrient addition experiment replicated across 26 sites spanning four continents, we demonstrated that climate variables were stronger predictors of leaf nitrogen content than soil nutrient supply. Leaf nitrogen increased more strongly with soil nitrogen supply in regions with the highest theoretical leaf nitrogen demand, increasing more in colder and drier environments than warmer and wetter environments. Thus, leaf nitrogen responses to nitrogen supply are primarily influenced by climatic gradients in photosynthetic nitrogen demand, an insight that could improve ESM predictions.

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Holocene vegetation dynamics of the Eastern Mediterranean region: Old controversies addressed by a new analysis - Esmeralda Cruz‐Silva; Sandy P. Harrison; I. Colin Prentice; Elena Marinova (Journal of Biogeography, 2024)
Aim We reconstruct vegetation changes since 12 ky in the Eastern Mediterranean to examine four features of the regional vegetation history that are controversial: the extent of non‐analogue vegetation assemblages in the transition from the Late Glacial to the early Holocene, the synchroneity of postglacial forest expansion, the geographical extent of temperate deciduous forest during the mid‐Holocene and the timing and trigger for the re‐establishment of drought‐tolerant vegetation during the late Holocene. Location The Eastern Mediterranean–Black Sea Caspian Corridor. Taxon Vascular plants. Methods We reconstruct vegetation changes for 122 fossil pollen records using a method that accounts for within‐biome variability in pollen taxon abundance to determine the biome with which a sample has greatest affinity. Per‐biome affinity threshold values were used to identify samples that do not belong to any modern biome. We apply time series analysis and mapping to examine space and time changes. Results Sites with non‐analogue vegetation were most common between 11.5 and 9.5 ky and mostly in the Carpathians. The transition from open vegetation to forest occurred at 10.64 ± 0.65 ky across the whole region. Temperate deciduous forest was not more extensive at 6 ky; maximum expansion occurred between 5.5 and 5 ky. Expansion of forest occurred between c. 4 and 2.8 k, followed by an abrupt decrease and a subsequent recovery. This pattern is not consistent with a systematic decline of forest towards more drought‐tolerant vegetation in the late Holocene but is consistent with centennial‐scale speleothem patterns linked to variations in moisture availability. Main Conclusions We show the occurrence of non‐analogue vegetation types peaked during early Holocene, forest expansion was synchronous across the region and there was an expansion of moisture‐demanding temperate trees around 5.5 to 5 ky. There is no signal of a continuous late Holocene aridification, but changes in forest cover appear to reflect climatic rather than anthropogenic influences.

Optimality-based modelling of wheat sowing dates globally - Shengchao Qiao; Sandy P. Harrison; I. Colin Prentice; Han Wang (Agricultural Systems, 2023)

Environmental controls on the light use efficiency of terrestrial gross primary production - Keith J. Bloomfield; Benjamin D. Stocker; Trevor F. Keenan; I. Colin Prentice (Global Change Biology, 2023)
Gross primary production (GPP) by terrestrial ecosystems is a key quantity in the global carbon cycle. The instantaneous controls of leaf‐level photosynthesis are well established, but there is still no consensus on the mechanisms by which canopy‐level GPP depends on spatial and temporal variation in the environment. The standard model of photosynthesis provides a robust mechanistic representation for C 3 species; however, additional assumptions are required to “scale up” from leaf to canopy. As a consequence, competing models make inconsistent predictions about how GPP will respond to continuing environmental change. This problem is addressed here by means of an empirical analysis of the light use efficiency (LUE) of GPP inferred from eddy covariance carbon dioxide flux measurements, in situ measurements of photosynthetically active radiation (PAR), and remotely sensed estimates of the fraction of PAR (fAPAR) absorbed by the vegetation canopy. Focusing on LUE allows potential drivers of GPP to be separated from its overriding dependence on light. GPP data from over 100 sites, collated over 20 years and located in a range of biomes and climate zones, were extracted from the FLUXNET2015 database and combined with remotely sensed fAPAR data to estimate daily LUE. Daytime air temperature, vapor pressure deficit, diffuse fraction of solar radiation, and soil moisture were shown to be salient predictors of LUE in a generalized linear mixed‐effects model. The same model design was fitted to site‐based LUE estimates generated by 16 terrestrial ecosystem models. The published models showed wide variation in the shape, the strength, and even the sign of the environmental effects on modeled LUE. These findings highlight important model deficiencies and suggest a need to progress beyond simple “goodness of fit” comparisons of inferred and predicted carbon fluxes toward an approach focused on the functional responses of the underlying dependencies.

A new method based on surface‐sample pollen data for reconstructing palaeovegetation patterns - Esmeralda Cruz‐Silva; Sandy P. Harrison; Elena Marinova; I. Colin Prentice (Journal of Biogeography, 2022)
Aim Biomisation has been the most widely used technique to reconstruct past regional vegetation patterns because it does not require an extensive modern pollen dataset. However, it has well‐known limitations including its dependence on expert judgement for the assignment of pollen taxa to plant functional types (PFTs) and PFTs to biomes. Here we present a new method that combines the strengths of biomisation with those of the alternative dissimilarity‐based techniques. Location The Eastern Mediterranean‐Black Sea Caspian Corridor (EMBSeCBIO). Taxon Plants Methods Modern pollen samples, assigned to biomes based on potential natural vegetation data, are used to characterize the within‐biome means and standard deviations of the abundances of each taxon. These values are used to calculate a dissimilarity index between any pollen sample and every biome, and thus assign the sample to the most likely biome. We calculate a threshold value for each modern biome; fossil samples with scores below the threshold for all modern biomes are thus identified as non‐analogue vegetation. We applied the new method to the EMBSeCBIO region to compare its performance with existing reconstructions. Results The method captured changes in the importance of individual taxa along environmental gradients. The balanced accuracy obtained for the EMBSeCBIO region using the new method was better than obtained using biomisation (77% vs. 65%). When the method was applied to high‐resolution fossil records, 70% of the entities showed more temporally stable biome assignments than obtained using biomisation. The technique also identified likely non‐analogue assemblages in a synthetic modern dataset and in fossil records. Main conclusions The new method yields more accurate and stable reconstructions of vegetation than biomisation. It requires an extensive modern pollen dataset, but is conceptually simple, and avoids subjective choices about taxon allocations to PFTs and PFTs to biomes.

The climatic space of European pollen taxa - Dongyang Wei; I. Colin Prentice; Sandy P. Harrison (Ecology, 2020)
Pollen data are widely used to reconstruct past climate changes, using relationships between modern pollen abundance in surface samples and climate at the surface‐sample sites as a calibration. Visualization of modern pollen data in multidimensional climate space provides a way to establish that taxon abundances are well behaved before using them in climate reconstructions. Visualization is also helpful for ecological interpretation of variations in pollen abundance in space and time. Here, we present Generalized Additive Models for the distribution of 195 European pollen and pteridophyte spore taxa in a bioclimate space defined by seasonal temperatures (as mean temperature of the coldest month and annual growing degree days) and an annual moisture index. These models can be used to explore the realized climate niche of pollen taxa and to build statistical models for palaeoclimate reconstruction. The data set is released under a Creative Commons BY license. When using the data set, we kindly request that you cite this article.

Acclimation of leaf respiration consistent with optimal photosynthetic capacity - Han Wang; Owen K. Atkin; Trevor F. Keenan; Nicholas G. Smith; Ian J. Wright; Keith J. Bloomfield; Jens Kattge; Peter B. Reich; I. Colin Prentice (Global Change Biology, 2020)
Plant respiration is an important contributor to the proposed positive global carbon‐cycle feedback to climate change. However, as a major component, leaf mitochondrial (‘dark’) respiration ( R d ) differs among species adapted to contrasting environments and is known to acclimate to sustained changes in temperature. No accepted theory explains these phenomena or predicts its magnitude. Here we propose that the acclimation of R d follows an optimal behaviour related to the need to maintain long‐term average photosynthetic capacity ( V cmax ) so that available environmental resources can be most efficiently used for photosynthesis. To test this hypothesis, we extend photosynthetic co‐ordination theory to predict the acclimation of R d to growth temperature via a link to V cmax , and compare predictions to a global set of measurements from 112 sites spanning all terrestrial biomes. This extended co‐ordination theory predicts that field‐measured R d and V cmax accessed at growth temperature ( R d,tg and V cmax,tg ) should increase by 3.7% and 5.5% per degree increase in growth temperature. These acclimated responses to growth temperature are less steep than the corresponding instantaneous responses, which increase 8.1% and 9.9% per degree of measurement temperature for R d and V cmax respectively. Data‐fitted responses proof indistinguishable from the values predicted by our theory, and smaller than the instantaneous responses. Theory and data are also shown to agree that the basal rates of both R d and V cmax assessed at 25°C ( R d,25 and V cmax,25 ) decline by ~4.4% per degree increase in growth temperature. These results provide a parsimonious general theory for R d acclimation to temperature that is simpler—and potentially more reliable—than the plant functional type‐based leaf respiration schemes currently employed in most ecosystem and land‐surface models.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Transforming conservation science and practice for a postnormal world - Matthew J. Colloff; Sandra Lavorel; Lorrae E. van Kerkhoff; Carina A. Wyborn; Ioan Fazey; Russell Gorddard; Georgina M. Mace; Wendy B. Foden; Michael Dunlop; I. Colin Prentice; John Crowley; Paul Leadley; et al. (Conservation Biology, 2017)
We examine issues to consider when reframing conservation science and practice in the context of global change. New framings of the links between ecosystems and society are emerging that are changing peoples’ values and expectations of nature, resulting in plural perspectives on conservation. Reframing conservation for global change can thus be regarded as a stage in the evolving relationship between people and nature rather than some recent trend. New models of how conservation links with transformative adaptation include how decision contexts for conservation can be reframed and integrated with an adaptation pathways approach to create new options for global‐change‐ready conservation. New relationships for conservation science and governance include coproduction of knowledge that supports social learning. New processes for implementing adaptation for conservation outcomes include deliberate practices used to develop new strategies, shift world views, work with conflict, address power and intergenerational equity in decisions, and build consciousness and creativity that empower agents to act. We argue that reframing conservation for global change requires scientists and practitioners to implement approaches unconstrained by discipline and sectoral boundaries, geopolitical polarities, or technical problematization. We consider a stronger focus on inclusive creation of knowledge and the interaction of this knowledge with societal values and rules is likely to result in conservation science and practice that meets the challenges of a postnormal world.

What have we learnt from palaeoclimate simulations? - Sandy P. Harrison; Patrick J. Bartlein; I. Colin Prentice (Journal of Quaternary Science, 2016)
There has been a gradual evolution in the way that palaeoclimate modelling and palaeoenvironmental data are used together to understand how the Earth System works, from an initial and largely descriptive phase through explicit hypothesis testing to diagnosis of underlying mechanisms. Analyses of past climate states are now regarded as integral to the evaluation of climate models, and have become part of the toolkit used to assess the likely realism of future projections. Palaeoclimate assessment has demonstrated that changes in large‐scale features of climate that are governed by the energy and water balance show consistent responses to changes in forcing in different climate states, and these consistent responses are reproduced by climate models. However, state‐of‐the‐art models are still largely unable to reproduce observed changes in climate at a regional scale reliably. While palaeoclimate analyses of state‐of‐the‐art climate models suggest an urgent need for model improvement, much work is also needed on extending and improving palaeoclimate reconstructions and quantifying and reducing both numerical and interpretative uncertainties.

Global effects of soil and climate on leaf photosynthetic traits and rates - Vincent Maire; Ian J. Wright; I. Colin Prentice; Niels H. Batjes; Radika Bhaskar; Peter M. van Bodegom; Will K. Cornwell; David Ellsworth; Ülo Niinemets; Alejandro Ordonez; Peter B. Reich; Louis S. Santiago (Global Ecology and Biogeography, 2015)
Aim The influence of soil properties on photosynthetic traits in higher plants is poorly quantified in comparison with that of climate. We address this situation by quantifying the unique and joint contributions to global leaf‐trait variation from soils and climate. Location Terrestrial ecosystems world‐wide. Methods Using a trait dataset comprising 1509 species from 288 sites, with climate and soil data derived from global datasets, we quantified the effects of 20 soil and 26 climate variables on light‐saturated photosynthetic rate ( A area ), stomatal conductance ( g s ), leaf nitrogen and phosphorus ( N area and P area ) and specific leaf area ( SLA ) using mixed regression models and multivariate analyses. Results Soil variables were stronger predictors of leaf traits than climatic variables, except for SLA . On average, N area , P area and A area increased and SLA decreased with increasing soil pH and with increasing site aridity. g s declined and P area increased with soil available P ( P avail ). N area was unrelated to total soil N . Joint effects of soil and climate dominated over their unique effects on N area and P area , while unique effects of soils dominated for A area and g s . Path analysis indicated that variation in A area reflected the combined independent influences of N area and g s , the former promoted by high pH and aridity and the latter by low P avail . Main conclusions Three environmental variables were key for explaining variation in leaf traits: soil pH and P avail , and the climatic moisture index (the ratio of precipitation to potential evapotranspiration). Although the reliability of global soil datasets lags behind that of climate datasets, our results nonetheless provide compelling evidence that both can be jointly used in broad‐scale analyses, and that effects uniquely attributable to soil properties are important determinants of leaf photosynthetic traits and rates. A significant future challenge is to better disentangle the covarying physiological, ecological and evolutionary mechanisms that underpin trait–environment relationships.

Balancing the costs of carbon gain and water transport: testing a new theoretical framework for plant functional ecology - I. Colin Prentice; Ning Dong; Sean M. Gleason; Vincent Maire; Ian J. Wright (Ecology Letters, 2014)
A novel framework is presented for the analysis of ecophysiological field measurements and modelling. The hypothesis ‘ leaves minimise the summed unit costs of transpiration and carboxylation ’ predicts leaf‐internal/ambient CO 2 ratios ( c i /c a ) and slopes of maximum carboxylation rate ( V cmax ) or leaf nitrogen ( N area ) vs . stomatal conductance. Analysis of data on woody species from contrasting climates (cold‐hot, dry‐wet) yielded steeper slopes and lower mean c i /c a ratios at the dry or cold sites than at the wet or hot sites. High atmospheric vapour pressure deficit implies low c i /c a in dry climates. High water viscosity (more costly transport) and low photorespiration (less costly photosynthesis) imply low c i /c a in cold climates. Observed site‐mean c i /c a shifts are predicted quantitatively for temperature contrasts (by photorespiration plus viscosity effects) and approximately for aridity contrasts. The theory explains the dependency of c i /c a ratios on temperature and vapour pressure deficit, and observed relationships of leaf δ 13 C and N area to aridity.

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Reconciling the optimal and empirical approaches to modelling stomatal conductance - Belinda E. Medlyn; Remko A. Duursma; Derek Eamus; David S. Ellsworth; I. Colin Prentice; Craig V. M. Barton; Kristine Y. Crous; Paolo de Angelis; Michael Freeman; Lisa Wingate (Global Change Biology, 2012)

CO 2 fertilization in temperate FACE experiments not representative of boreal and tropical forests - THOMAS HICKLER; BENJAMIN SMITH; I. COLIN PRENTICE; KRISTINA MJÖFORS; PAUL MILLER; ALMUT ARNETH; MARTIN T. SYKES (Global Change Biology, 2008)
Results from free‐air CO 2 enrichment (FACE) experiments in temperate climates indicate that the response of forest net primary productivity (NPP) to elevated CO 2 might be highly conserved across a broad range of productivities. In this study, we show that the LPJ‐GUESS dynamic vegetation model reproduces the magnitude of the NPP enhancement at temperate forest FACE experiments. A global application of the model suggests that the response found in the experiments might also be representative of the average response of forests globally. However, the predicted NPP enhancement in tropical forests is more than twice as high as in boreal forests, suggesting that currently available FACE results are not applicable to these ecosystems. The modeled geographic pattern is to a large extent driven by the temperature dependence of the relative affinities of the primary assimilation enzyme (Rubisco) for CO 2 and O 2 .

Projected Changes in Terrestrial Carbon Storage in Europe under Climate and Land-use Change, 1990–2100 - Sönke Zaehle; Alberte Bondeau; Timothy R. Carter; Wolfgang Cramer; Markus Erhard; I. Colin Prentice; I. Reginster; Mark D. A. Rounsevell; Stephen Sitch; Benjamin Smith; Pascalle C. Smith; Martin Sykes (Ecosystems, 2007)

Implementing plant hydraulic architecture within the LPJ Dynamic Global Vegetation Model - Thomas Hickler; I. Colin Prentice; Benjamin Smith; Martin T. Sykes; Sönke Zaehle (Global Ecology and Biogeography, 2006)
Aim To implement plant hydraulic architecture within the Lund–Potsdam–Jena Dynamic Global Vegetation Model (LPJ–DGVM), and to test the model against a set of observational data. If the model can reproduce major patterns in vegetation and ecosystem processes, we consider this to be an important linkage between plant physiology and larger‐scale ecosystem dynamics. Location The location is global, geographically distributed. Methods A literature review was carried out to derive model formulations and parameter values for representing the hydraulic characteristics of major global plant functional types (PFTs) in a DGVM. After implementing the corresponding formulations within the LPJ–DGVM, present‐day model output was compared to observational data. Results The model reproduced observed broad‐scale patterns in potential natural vegetation, but it failed to distinguish accurately between different types of grassland and savanna vegetation, possibly related to inadequate model representations of water fluxes in the soil and wildfire effects. Compared to a version of the model using an empirical formulation for calculating plant water supply without considering plant hydraulic architecture, the new formulation improved simulated patterns of vegetation in particular for dry shrublands. Global‐scale simulation results for runoff and actual evapotranspiration (AET) corresponded well to available data. The model also successfully reproduced the magnitude and seasonal cycle of AET for most EUROFLUX forests, while modelled variation in NPP across a large number of sites spanning several biomes showed a strong correlation with estimates from field measurements. Main conclusions The model was generally confirmed by comparison to observational data. The novel model representation of water flow within plants makes it possible to resolve mechanistically the effects of hydraulic differences between plant functional groups on vegetation structure, water cycling, and competition. This may be an advantage when predicting ecosystem responses to nonextant climates, in particular in areas dominated by dry shrubland vegetation.

Implementing plant hydraulic architecture within the LPJ Dynamic Global Vegetation Model - Thomas Hickler; I. Colin Prentice; Benjamin Smith; Martin T. Sykes; Sonke Zaehle (Global Ecology and Biogeography, 2006)

Terrestrial biosphere carbon storage under alternative climate projections - Sibyll Schaphoff; Wolfgang Lucht; Dieter Gerten; Stephen Sitch; Wolfgang Cramer; I. Colin Prentice (Climatic Change, 2006)

Comparing and evaluating process‐based ecosystem model predictions of carbon and water fluxes in major European forest biomes - Pablo Morales; Martin T. Sykes; I. Colin Prentice; Pete Smith; Benjamin Smith; Harald Bugmann; Bärbel Zierl; Pierre Friedlingstein; Nicolas Viovy; Santi Sabaté; Anabel Sánchez; Eduard Pla; et al. (Global Change Biology, 2005)
Process‐based models can be classified into: (a) terrestrial biogeochemical models (TBMs), which simulate fluxes of carbon, water and nitrogen coupled within terrestrial ecosystems, and (b) dynamic global vegetation models (DGVMs), which further couple these processes interactively with changes in slow ecosystem processes depending on resource competition, establishment, growth and mortality of different vegetation types. In this study, four models – RHESSys, GOTILWA+, LPJ‐GUESS and ORCHIDEE – representing both modelling approaches were compared and evaluated against benchmarks provided by eddy‐covariance measurements of carbon and water fluxes at 15 forest sites within the EUROFLUX project. Overall, model‐measurement agreement varied greatly among sites. Both modelling approaches have somewhat different strengths, but there was no model among those tested that universally performed well on the two variables evaluated. Small biases and errors suggest that ORCHIDEE and GOTILWA+ performed better in simulating carbon fluxes while LPJ‐GUESS and RHESSys did a better job in simulating water fluxes. In general, the models can be considered as useful tools for studies of climate change impacts on carbon and water cycling in forests. However, the various sources of variation among models simulations and between models simulations and observed data described in this study place some constraints on the results and to some extent reduce their reliability. For example, at most sites in the Mediterranean region all models generally performed poorly most likely because of problems in the representation of water stress effects on both carbon uptake by photosynthesis and carbon release by heterotrophic respiration ( R h ). The use of flux data as a means of assessing key processes in models of this type is an important approach to improving model performance. Our results show that the models have value but that further model development is necessary with regard to the representation of the some of the key ecosystem processes.

Ecosystem dynamics based on plankton functional types for global ocean biogeochemistry models - Corinne Le Quéré; Sandy P. Harrison; I. Colin Prentice; Erik T. Buitenhuis; Olivier Aumont; Laurent Bopp; Hervé Claustre; Leticia Cotrim Da Cunha; Richard Geider; Xavier Giraud; Christine Klaas; Karen E. Kohfeld; et al. (Global Change Biology, 2005)
Ecosystem processes are important determinants of the biogeochemistry of the ocean, and they can be profoundly affected by changes in climate. Ocean models currently express ecosystem processes through empirically derived parameterizations that tightly link key geochemical tracers to ocean physics. The explicit inclusion of ecosystem processes in models will permit ecological changes to be taken into account, and will allow us to address several important questions, including the causes of observed glacial–interglacial changes in atmospheric trace gases and aerosols, and how the oceanic uptake of CO 2 is likely to change in the future. There is an urgent need to assess our mechanistic understanding of the environmental factors that exert control over marine ecosystems, and to represent their natural complexity based on theoretical understanding. We present a prototype design for a Dynamic Green Ocean Model (DGOM) based on the identification of (a) key plankton functional types that need to be simulated explicitly to capture important biogeochemical processes in the ocean; (b) key processes controlling the growth and mortality of these functional types and hence their interactions; and (c) sources of information necessary to parameterize each of these processes within a modeling framework. We also develop a strategy for model evaluation, based on simulation of both past and present mean state and variability, and identify potential sources of validation data for each. Finally, we present a DGOM‐based strategy for addressing key questions in ocean biogeochemistry. This paper thus presents ongoing work in ocean biogeochemical modeling, which, it is hoped will motivate international collaborations to improve our understanding of the role of the ocean in the climate system.

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Sensitivity of a dynamic global vegetation model to climate and atmospheric CO 2 - Stefan Gerber; Fortunat Joos; I. Colin Prentice (Global Change Biology, 2004)
The equilibrium carbon storage capacity of the terrestrial biosphere has been investigated by running the Lund–Potsdam–Jena Dynamic Global Vegetation Model to equilibrium for a range of CO 2 concentrations and idealized climate states. Local climate is defined by the combination of an observation‐based climatology and perturbation patterns derived from a 4 × CO 2 warming simulations, which are linearly scaled to global mean temperature deviations, Δ T glob . Global carbon storage remains close to its optimum for Δ T glob in the range of ±3°C in simulations with constant atmospheric CO 2 . The magnitude of the carbon loss to the atmosphere per unit change in global average surface temperature shows a pronounced nonlinear threshold behavior. About twice as much carbon is lost per degree warming for Δ T glob above 3°C than for present climate. Tropical, temperate, and boreal trees spread poleward with global warming. Vegetation dynamics govern the distribution of soil carbon storage and turnover in the climate space. For cold climate conditions, the global average decomposition rate of litter and soil decreases with warming, despite local increases in turnover rates. This result is not compatible with the assumption, commonly made in global box models, that soil turnover increases exponentially with global average surface temperature, over a wide temperature range.

Climate and CO 2 controls on global vegetation distribution at the last glacial maximum: analysis based on palaeovegetation data, biome modelling and palaeoclimate simulations - SANDY P. HARRISON; COLIN I. PRENTICE (Global Change Biology, 2003)
The global vegetation response to climate and atmospheric CO 2 changes between the last glacial maximum and recent times is examined using an equilibrium vegetation model (BIOME4), driven by output from 17 climate simulations from the Palaeoclimate Modelling Intercomparison Project. Features common to all of the simulations include expansion of treeless vegetation in high northern latitudes; southward displacement and fragmentation of boreal and temperate forests; and expansion of drought‐tolerant biomes in the tropics. These features are broadly consistent with pollen‐based reconstructions of vegetation distribution at the last glacial maximum. Glacial vegetation in high latitudes reflects cold and dry conditions due to the low CO 2 concentration and the presence of large continental ice sheets. The extent of drought‐tolerant vegetation in tropical and subtropical latitudes reflects a generally drier low‐latitude climate. Comparisons of the observations with BIOME4 simulations, with and without consideration of the direct physiological effect of CO 2 concentration on C 3 photosynthesis, suggest an important additional role of low CO 2 concentration in restricting the extent of forests, especially in the tropics. Global forest cover was overestimated by all models when climate change alone was used to drive BIOME4, and estimated more accurately when physiological effects of CO 2 concentration were included. This result suggests that both CO 2 effects and climate effects were important in determining glacial‐interglacial changes in vegetation. More realistic simulations of glacial vegetation and climate will need to take into account the feedback effects of these structural and physiological changes on the climate.

Maximum impacts of future reforestation or deforestation on atmospheric CO 2 - JOANNA I. HOUSE; I. COLIN PRENTICE; CORINNE LE QUÉRÉ (Global Change Biology, 2002)
There is scope for land‐use changes to increase or decrease CO 2 concentrations in the atmosphere over the next century. Here we make simple but robust calculations of the maximum impact of such changes. Historical land‐use changes (mostly deforestation) and fossil fuel emissions have caused an increase in atmospheric concentration of CO 2 of 90 ppm between the pre‐industrial era and year 2000. The projected range of CO 2 concentrations in 2100, under a range of emissions scenarios developed for the IPCC, is 170–600 ppm above 2000 levels. This range is mostly due to different assumptions regarding fossil fuel emissions. If all of the carbon so far released by land‐use changes could be restored to the terrestrial biosphere, atmospheric CO 2 concentration at the end of the century would be about 40–70 ppm less than it would be if no such intervention had occurred. Conversely, complete global deforestation over the same time frame would increase atmospheric concentrations by about 130–290 ppm. These are extreme assumptions; the maximum feasible reforestation and afforestation activities over the next 50 years would result in a reduction in CO 2 concentration of about 15–30 ppm by the end of the century. Thus the time course of fossil fuel emissions will be the major factor in determining atmospheric CO 2 concentrations for the foreseeable future.

Growth enhancement due to global atmospheric change as predicted by terrestrial ecosystem models: consistent with US forest inventory data - Fortunat Joos; I. Colin Prentice; Joanna I. House (Global Change Biology, 2002)
Small reported growth enhancement factors based on analyses of forest inventory data from the eastern USA ( Caspersen et al . 2000 , Science, 290, 1148–1151) have been interpreted as evidence against CO 2 fertilization in natural forests. We show to the contrary that growth enhancement in response to rising CO 2 , as found in ecosystems with experimental CO 2 enrichment and implemented in terrestrial ecosystem models, is consistent with the data that have been presented within their uncertainties. Comparing forest inventory data with results of an empirical model of age‐dependent biomass accumulation, we find that growth enhancement of plausible magnitude could not be detected in these data, even if it were present. Although forest regrowth due to land‐use change is recognized as an important cause of carbon uptake by eastern US forests, forest inventory data do not provide a basis for eliminating environmentally induced growth enhancement as a substantial contribution to the global terrestrial carbon sink.

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Representation of vegetation dynamics in the modelling of terrestrial ecosystems: comparing two contrasting approaches within European climate space - Benjamin Smith; I. Colin Prentice; Martin T. Sykes (Global Ecology and Biogeography, 2001)
Advances in dynamic ecosystem modelling have made a number of different approaches to vegetation dynamics possible. Here we compare two models representing contrasting degrees of abstraction of the processes governing dynamics in real vegetation. Model (a) (GUESS) simulates explicitly growth and competition among individual plants. Differences in crown structure (height, depth, area and LAI) influence relative light uptake by neighbours. Assimilated carbon is allocated individually by each plant to its leaf, fine root and sapwood tissues. Carbon allocation and turnover of sapwood to heartwood in turn govern height and diameter growth. Model (b) (LPJ) incorporates a ‘dynamic global vegetation model’ (DGVM) architecture, simulating growth of populations of plant functional types (PFTs) over a grid cell, integrating individual‐level processes over the proportional area (foliar projective cover, FPC) occupied by each PFT. Individual plants are not simulated, but are replaced by explicit parameterizations of their growth and interactions. The models are identical in their representation of core physiological and biogeochemical processes. Both also use the same set of PFTs, corresponding to the major woody plant groups in Europe, plus a grass type. When applied at a range of locations, broadly spanning climatic variation within Europe, both models successfully predicted PFT composition and succession within modern natural vegetation. However, the individual‐based model performed better in areas where deciduous and evergreen types coincide, and in areas subject to pronounced seasonal water deficits, which would tend to favour grasses over drought‐intolerant trees. Differences in model performance could be traced to their treatment of individual‐level processes, in particular light competition and stress‐induced mortality. Our results suggest that an explicit individual‐based approach to vegetation dynamics may be an advantage in modelling of ecosystem structure and function at the resolution required for regional‐ to continental‐scale studies.

An introduction to the European Terrestrial Ecosystem Modelling Activity - Martin T. Sykes; I. Colin Prentice; Benjamin Smith; Wolfgang Cramer; Sergey Venevsky (Global Ecology and Biogeography, 2001)
The objective of the European Terrestrial Ecosystem Modelling Activity (ETEMA) was to address some of the major challenges in developing generalized models to examine responses of natural and seminatural ecosystems to environmental change at the regional to European scale. The approach described herein was to break down the totality of ecosystem functioning into its key components, each with its characteristic spatial and temporal scales. A conceptual framework was developed describing the configuration of these components as modules within a generalized simulation model. The framework describes the key inputs, outputs and state variables, their spatial and temporal contexts, and information flows between modules. The ‘backbone’ of the model is a system of nested timing loops corresponding to the disparate time scales at which different ecosystem processes occur. The framework is a theoretical construct into which ecosystem models at levels of complexity ranging from the very general to the highly detailed can be mapped, and thus provides a guide for development of models for novel, particularly regional‐scale, applications. A number of subsystem studies of the major components of ecosystem functioning, i.e. modules of the conceptual framework, are briefly introduced herein. The general aim of the subsystem studies was to identify the key alternative formulations (as opposed to minor variants) and test these against observational data. The various subsystem studies concern planetary boundary layer–ecosystem interactions, ecosystem CO 2 and H 2 O fluxes, vegetation physiology and phenology, biogeography and vegetation dynamics, detritus and SOM dynamics, soil moisture and human and natural disturbances and, as individual papers, they complete this special ETEMA issue.

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Modelling the vegetation of China using the process‐based equilibrium terrestrial biosphere model BIOME3 - Jian Ni; Martin T. Sykes; I. Colin Prentice; Wolfgang Cramer (Global Ecology and Biogeography, 2000)
1 We model the potential vegetation and annual net primary production (NPP) of China on a 10′ grid under the present climate using the processed‐based equilibrium terrestrial biosphere model BIOME3. The simulated distribution of the vegetation was in general in good agreement with the potential natural vegetation based on a numerical comparison between the two maps using the ΔV statistic (ΔV = 0.23). Predicted and measured NPP were also similar, especially in terms of biome‐averages. 2 A coupled ocean–atmosphere general circulation model including sulphate aerosols was used to drive a double greenhouse gas scenario for 2070–2099. Simulated vegetation maps from two different CO 2 scenarios (340 and 500 p.p.m.v.) were compared to the baseline biome map using ΔV. Climate change alone produced a large reduction in desert, alpine tundra and ice/polar desert, and a general pole‐ward shift of the boreal, temperate deciduous, warm–temperate evergreen and tropical forest belts, a decline in boreal deciduous forest and the appearance of tropical deciduous forest. The inclusion of CO 2 physiological effects led to a marked decrease in moist savannas and desert, a general decrease for grasslands and steppe, and disappearance of xeric woodland/scrub. Temperate deciduous broadleaved forest, however, shifted north to occupy nearly half the area of previously temperate mixed forest. 3 The impact of climate change and increasing CO 2 is not only on biogeography, but also on potential NPP. The NPP values for most of the biomes in the scenarios with CO 2 set at 340 p.p.m.v. and 500 p.p.m.v. are greater than those under the current climate, except for the temperate deciduous forest, temperate evergreen broadleaved forest, tropical rain forest, tropical seasonal forest, and xeric woodland/scrub biomes. Total vegetation and total carbon is simulated to increase significantly in the future climate scenario, both with and without the CO 2 direct physiological effect. 4 Our results show that the global process‐based equilibrium terrestrial biosphere model BIOME3 can be used successfully at a regional scale.

Mid‐Holocene and glacial‐maximum vegetation geography of the northern continents and Africa - I. Colin Prentice; Dominique Jolly (Journal of Biogeography, 2000)
BIOME 6000 is an international project to map vegetation globally at mid‐Holocene (6000 14 C yr bp ) and last glacial maximum (LGM, 18,000 14 C yr bp ), with a view to evaluating coupled climate‐biosphere model results. Primary palaeoecological data are assigned to biomes using an explicit algorithm based on plant functional types. This paper introduces the second Special Feature on BIOME 6000. Site‐based global biome maps are shown with data from North America, Eurasia (except South and Southeast Asia) and Africa at both time periods. A map based on surface samples shows the method’s skill in reconstructing present‐day biomes. Cold and dry conditions at LGM favoured extensive tundra and steppe. These biomes intergraded in northern Eurasia. Northern hemisphere forest biomes were displaced southward. Boreal evergreen forests (taiga) and temperate deciduous forests were fragmented, while European and East Asian steppes were greatly extended. Tropical moist forests (i.e. tropical rain forest and tropical seasonal forest) in Africa were reduced. In south‐western North America, desert and steppe were replaced by open conifer woodland, opposite to the general arid trend but consistent with modelled southward displacement of the jet stream. The Arctic forest limit was shifted slighly north at 6000 14 C yr bp in some sectors, but not in all. Northern temperate forest zones were generally shifted greater distances north. Warmer winters as well as summers in several regions are required to explain these shifts. Temperate deciduous forests in Europe were greatly extended, into the Mediterranean region as well as to the north. Steppe encroached on forest biomes in interior North America, but not in central Asia. Enhanced monsoons extended forest biomes in China inland and Sahelian vegetation into the Sahara while the African tropical rain forest was also reduced, consistent with a modelled northward shift of the ITCZ and a more seasonal climate in the equatorial zone. Palaeobiome maps show the outcome of separate, independent migrations of plant taxa in response to climate change. The average composition of biomes at LGM was often markedly different from today. Refugia for the temperate deciduous and tropical rain forest biomes may have existed offshore at LGM, but their characteristic taxa also persisted as components of other biomes. Examples include temperate deciduous trees that survived in cool mixed forest in eastern Europe, and tropical evergreen trees that survived in tropical seasonal forest in Africa. The sequence of biome shifts during a glacial‐interglacial cycle may help account for some disjunct distributions of plant taxa. For example, the now‐arid Saharan mountains may have linked Mediterranean and African tropical montane floras during enhanced monsoon regimes. Major changes in physical land‐surface conditions, shown by the palaeobiome data, have implications for the global climate. The data can be used directly to evaluate the output of coupled atmosphere‐biosphere models. The data could also be objectively generalized to yield realistic gridded land‐surface maps, for use in sensitivity experiments with atmospheric models. Recent analyses of vegetation‐climate feedbacks have focused on the hypothesized positive feedback effects of climate‐induced vegetation changes in the Sahara/Sahel region and the Arctic during the mid‐Holocene. However, a far wider spectrum of interactions potentially exists and could be investigated, using these data, both for 6000 14 C yr bp and for the LGM.

Quantifying the Impact of Global Climate Change on Potential Natural Vegetation - Martin T. Sykes; I. Colin Prentice; Fouzia Laarif (Climatic Change, 1999)

BIOME 6000: reconstructing global mid‐Holocene vegetation patterns from palaeoecological records - I. Colin Prentice; Thompson Webb III (Journal of Biogeography, 1998)
Global change research needs data sets describing past states of the Earth system. Vegetation distributions for specified ‘time slices’ (with known forcings, such as changes in insolation patterns due to the Earth's orbital variations, changes in the extent of ice‐sheets, and changes in atmospheric trace‐gas composition) should provide a benchmark for coupled climate‐biosphere models. Pollen and macrofossil records from dated sediments give spatially extensive coverage of data on vegetation distribution changes. Applications of such data have been delayed by the lack of a global synthesis. The BIOME 6000 project of IGBP aims at a synthesis for 6000 years bp. Success depends on community‐wide participation for data compilation and quality assurance, and on a robust methodology for assigning palaeorecords to biomes. In the method summarized here, taxa are assigned to one or more plant functional types (PFTs) and biomes reconstructed using PFT‐based definitions. By involving regional experts in PFT assignments, one can combine data from different floras without compromising global consistency in biome assignments. This article introduces a series of articles that substantially extend the BIOME 6000 data set. The list of PFTs and the reconstruction procedure itself are evolving. Some compromises (for example, restricted taxon lists in some regions) limit the precision of biome assignments and will become obsolete as primary data are put into community data bases. This trend will facilitate biome mapping for other time slices. Co‐evolution of climate‐biosphere modelling and palaeodata synthesis and analysis will continue.

Present‐day and mid‐Holocene biomes reconstructed from pollen and plant macrofossil data from the former Soviet Union and Mongolia - Pavel E. Tarasov; Thompson Webb III; Andrei A. Andreev; Natalya B. Afanas’eva; Natalya A. Berezina; Ludmila G. Bezusko; Tatyana A. Blyakharchuk; Natalia S. Bolikhovskaya; Rachid Cheddadi; Margarita M. Chernavskaya; Galina M. Chernova; Nadezhda I. Dorofeyuk; et al. (Journal of Biogeography, 1998)
Fossil pollen data supplemented by tree macrofossil records were used to reconstruct the vegetation of the Former Soviet Union and Mongolia at 6000 years. Pollen spectra were assigned to biomes using the plant‐functional‐type method developed by Prentice et al . (1996). Surface pollen data and a modern vegetation map provided a test of the method. This is the first time such a broad‐scale vegetation reconstruction for the greater part of northern Eurasia has been attempted with objective techniques. The new results confirm previous regional palaeoenvironmental studies of the mid‐Holocene while providing a comprehensive synopsis and firmer conclusions. West of the Ural Mountains temperate deciduous forest extended both northward and southward from its modern range. The northern limits of cool mixed and cool conifer forests were also further north than present. Taiga was reduced in European Russia, but was extended into Yakutia where now there is cold deciduous forest. The northern limit of taiga was extended (as shown by increased Picea pollen percentages, and by tree macrofossil records north of the present‐day forest limit) but tundra was still present in north‐eastern Siberia. The boundary between forest and steppe in the continental interior did not shift substantially, and dry conditions similar to present existed in western Mongolia and north of the Aral Sea.

Biome reconstruction from pollen and plant macrofossil data for Africa and the Arabian peninsula at 0 and 6000 years - Dominique Jolly; I. Colin Prentice; Raymonde Bonnefille; Aziz Ballouche; Martin Bengo; Patrice Brenac; Guillaume Buchet; David Burney; Jean‐Pierre Cazet; Rachid Cheddadi; Therese Edorh; Hilaire Elenga; et al. (Journal of Biogeography, 1998)
Biome reconstruction from pollen and plant macrofossil data provides an objective method to reconstruct past vegetation. Biomes for Africa and the Arabian peninsula have been mapped for 6000 years bp and provide a new standard for the evaluation of simulated palaeovegetation distributions. A test using modern pollen data shows the robustness of the biomization method, which is able to predict the major vegetation types with a high confidence level. The application of the procedure to the 6000 years data set (pollen and plant macrofossil analyses) shows systematic differences from the present that are consistent with the numerous previous regional and continental interpretations, while providing a more extensive and more objective basis for such interpretations. Madagascar, eastern, southern and central Africa show only minor changes in terms of biomes, compared to present. Major changes in biome distributions occur north of 15°N, with steppe in many low‐elevation sites that are now desert, and temperate xerophytic woods/scrub and warm mixed forest in the Saharan mountains. These shifts in biome distributions imply significant changes in climate, especially precipitation, between 6000 years and present, reflecting a change in monsoon extent combined with a southward expansion of Mediterranean influence.

Pollen‐based biome reconstructions for China at 0 and 6000 years - Ge Yu; I. Colin Prentice; Sandy P. Harrison; Xiangjun Sun (Journal of Biogeography, 1998)
Biomization provides an objective and robust method of assigning pollen spectra to biomes so that pollen data can be mapped and compared directly with the output of biomgeographic models. We have tested the applicability of this procedure, originally developed for Europe, to assign modern surface samples from China to biomes. The procedure successfully delineated the major vegetation types of China. When the same procedure was applied to fossil pollen samples for 6000 years ago, the reconstructions showed systematic differences from present, consistent with previous interpretations of vegetation changes since the mid‐Holocene. In eastern China, the forest zones were systematically shifted northwards, such that cool mixed forests displaced taiga in northeastern China, while broad‐leaved evergreen forest extended c . 300 km and temperate deciduous forest c . 500–600 km beyond their present northern limits. In northwestern China, the area of desert and steppe vegetation was reduced compared to present. On the Tibetan Plateau, forest vegetation extended to higher elevations than today and the area of tundra was reduced. These shifts in biome distributions imply significant changes in climate since 6000 years ago that can be interpreted qualitatively as a response to orbital forcing and its secondary effects on the Asian monsoon.

Coupling dynamic models of climate and vegetation - JONATHAN A. FOLEY; SAMUEL LEVIS; COLIN I. PRENTICE; DAVID POLLARD; STARLEY L. THOMPSON (Global Change Biology, 1998)

Coupling dynamic models of climate and vegetation - Jonathan A. Foley; Samuel Levis; I. Colin Prentice; David Pollard; Starley L. Thompson (Global Change Biology, 1998)
Numerous studies have underscored the importance of terrestrial ecosystems as an integral component of the Earth's climate system. This realization has already led to efforts to link simple equilibrium vegetation models with Atmospheric General Circulation Models through iterative coupling procedures. While these linked models have pointed to several possible climate–vegetation feedback mechanisms, they have been limited by two shortcomings: (i) they only consider the equilibrium response of vegetation to shifting climatic conditions and therefore cannot be used to explore transient interactions between climate and vegetation; and (ii) the representations of vegetation processes and land‐atmosphere exchange processes are still treated by two separate models and, as a result, may contain physical or ecological inconsistencies. Here we present, as a proof concept, a more tightly integrated framework for simulating global climate and vegetation interactions. The prototype coupled model consists of the GENESIS (version 2) Atmospheric General Circulation Model and the IBIS (version 1) Dynamic Global Vegetation Model. The two models are directly coupled through a common treatment of land surface and ecophysiological processes, which is used to calculate the energy, water, carbon, and momentum fluxes between vegetation, soils, and the atmosphere. On one side of the interface, GENESIS simulates the physics and general circulation of the atmosphere. On the other side, IBIS predicts transient changes in the vegetation structure through changes in the carbon balance and competition among plants within terrestrial ecosystems. As an initial test of this modelling framework, we perform a 30 year simulation in which the coupled model is supplied with modern CO 2 concentrations, observed ocean temperatures, and modern insolation. In this exploratory study, we run the GENESIS atmospheric model at relatively coarse horizontal resolution (4.5° latitude by 7.5° longitude) and IBIS at moderate resolution (2° latitude by 2° longitude). We initialize the models with globally uniform climatic conditions and the modern distribution of potential vegetation cover. While the simulation does not fully reach equilibrium by the end of the run, several general features of the coupled model behaviour emerge. We compare the results of the coupled model against the observed patterns of modern climate. The model correctly simulates the basic zonal distribution of temperature and precipitation, but several important regional biases remain. In particular, there is a significant warm bias in the high northern latitudes, and cooler than observed conditions over the Himalayas, central South America, and north‐central Africa. In terms of precipitation, the model simulates drier than observed conditions in much of South America, equatorial Africa and Indonesia, with wetter than observed conditions in northern Africa and China. Comparing the model results against observed patterns of vegetation cover shows that the general placement of forests and grasslands is roughly captured by the model. In addition, the model simulates a roughly correct separation of evergreen and deciduous forests in the tropical, temperate and boreal zones. However, the general patterns of global vegetation cover are only approximately correct: there are still significant regional biases in the simulation. In particular, forest cover is not simulated correctly in large portions of central Canada and southern South America, and grasslands extend too far into northern Africa. These preliminary results demonstrate the feasibility of coupling climate models with fully dynamic representations of the terrestrial biosphere. Continued development of fully coupled climate‐vegetation models will facilitate the exploration of a broad range of global change issues, including the potential role of vegetation feedbacks within the climate system, and the impact of climate variability and transient climate change on the terrestrial biosphere.